Epiphany in Sudden Fiction - Koçsoy, F.gül (Tekirdağ Namık Kemal Üniversitesi, 2018)
This study aims at finding the common points between epiphany as a literary concept and sudden fiction genre and demonstrating them through sample stories. Epiphany which is the means/technique/experience of explaining spiritual insights has ontological feature and shares with philosophical and open-ended sudden fiction momentary perception, poetic nature and the power of leading to the permanent changes in behaviours.  Both in epiphany and sudden fiction, seemingly ordinary and known phenomena, with their different aspects are shown and the individual experiences gain universal particularity. The common purpose of epiphany and sudden fiction is to make the reader sense the truths about the essence of life/being, adopt new points of view and gain the habit of exercising this process for other experiences. The epiphany in sudden fiction, like the ones in other genres, begins at the ending/closure leaving a shocking impact on the reader. It motives her/him to experience a rapid emotional and intellectual process and to produce new understandings, values and beliefs on the particular event/phenomenon and to internalize them.  In this context, sudden fiction directly reminds us of epiphany. With its concise texture, it prescribes that accepted truths should be questioned and rebuilt by new views. The reader, by experiencing epiphany, will once again remember that truths are relative and see that evaluating events/phenomena by different views affects life positively. This is the main function of literature; epiphany and sudden fiction actualize this function together.

Bu çalışma, edebi bir kavram olarak epifan ile küçürek öykü türü arasındaki ortak noktaları bulmayı ve örnek öykülerle bunları göstermeyi amaçlar. Anlık idrak, şiirsellik ve kalıcı davranış değişikliklerine yöneltme gücü, hem tinsel açılımları ifade etme aracı/tekniği/deneyimi olan ve ontolojik niteliğe sahip epifanda, hem de felsefi içerikli ve açık uçlu olan küçürek öyküde mevcuttur. Epifan ve küçürek öyküde sıradan ve bilindik görünen olgular farklı boyutlarıyla göz önüne serilir ve bireysel boyutta yaşanan deneyimler evrensellik kazanır. Epifan ve küçürek öykünün ortak amacı okuyucuya yaşamın/varlığın özüyle ilgili hakikatleri duyumsatıp yeni bakış açılarını benimsetmek ve bu süreci başka deneyimler için de uygulama alışkanlığı kazandırmaktır. Tıpkı diğer türlerdeki epifanlar gibi küçürek öyküde yer alan epifan da, metnin sonlandığı/kapandığı noktada okuyucuda sarsıcı bir etki bırakarak başlar, onun hızlı bir duygusal ve düşünsel süreci deneyimlemesine neden olur ve sonrasında söz konusu olay veya olguya dair yeni anlamalar, değerler ve inançlar üretip onları içselleştirmesini sağlar. Bu bağlamda küçürek öykü doğrudan epifanı çağrıştırmaktadır. Az ve öz yapısıyla kabul edilmiş gerçeklerin sorgulanması ve farklı açılarla yeniden inşasını öngörmektedir. Okur, epifan yaşayarak gerçeklerin göreceli olduğunu bir kez daha anımsayacak ve olay/olgulara farklı açılardan bakmanın yaşamı olumlu yönde etkilediğini görecektir. Bu ise edebiyatın temel işlevidir; epifan ve küçürek öykü bu işlevi birlikte yerine getirmektedir.
Küçürek Öyküde Epifan